Atomistic real-space observation of the van der Waals layered structure and tailored morphology in VSe2. Issue 2 (19th December 2018) - Lee, Sunghun; Kim, Jinsu; Park, Yun Chang; Chun, Seung-Hyun
Abstract : The morphology of VSe2, identified as a 1T-phase in atomistic real-space, can be tailored simply by controlling the carrier gas flow rate. Abstract : Two-dimensional (2D) transition metal dichalcogenides with van der Waals gaps have attracted much attention due to their peculiarly distinctive physical properties from their bulk counterparts. Among them, vanadium diselenide (VSe2 ) has been considered to be a promising candidate for future spintronic devices, as room temperature ferromagnetism was reported recently. However, detailed crystallography and properties of VSe2 nanosheets have been less explored. Here, we report the atomistic real-space observation of the van der Waals layered structure of VSe2 for the first time. Furthermore, simply by controlling the carrier gas flow rate, a morphological variation of the surface area and thickness of VSe2 nanosheets was observed. The room temperature ferromagnetic feature of single VSe2 nanosheets was also revealed by magnetic force microscopy measurements. Our findings will play a significant role in the research of intrinsic 2D ferromagnetic materials.